Psoriasis - a review of recent progress, characteristics, diagnostic management - Warzyszak, Paweł; Małek, Róża; Milczek, Maria; Żołyniak, Wojciech; Tomasik, Mikołaj; Hawranik, Izabela; Niski, Szymon; Żaba, Ziemowit; Lisowska, Aleksandra (Journal of Education, Health and Sport, 2022)
Introduction: Psoriasis is a common, chronic, systemic inflammatory disease with an immunological basis. It occurs in about 2% of people in Europe and North America. It is associated with an increased probability of obesity, diabetes, dyslipidemia, cardiovascular disease and inflammatory bowel disease. Objective: The purpose of this review is to analyze the latest information on the characteristics, diagnosis and treatment of patients with psoriasis. Materials and methods: The present study was based on available data collected in the PubMed database and published between 2001 and 2022. The study was conducted by reviewing keywords such as: "psoriasis," "diagnosis," "treatment," "genetics," "immunology," "angiogenesis," "keratinocytes," and "incidence." State of the knowledge: In the last decade, biologic drugs targeting tumor necrosis factor alpha, interleukin 23, interleukin 17 and interleukin 12 have been developed and approved for the treatment of psoriasis. These drugs have revolutionized the treatment and management of psoriasis. Summary: Over the past decade, there have been tremendous advances in knowledge about the pathogenesis of psoriasis. Discoveries on this background, have given rise to new biological therapies. Currently in clinical trials are substances such as, Janus kinase inhibitors and tyrosine kinase 2 inhibitors, which represent hope for the most affected patients. Unfortunately, our knowledge of the causes of psoriasis is still incomplete. This poses a challenge for further research and thus the creation of more therapeutic substances.